Governments and industry include pathways for sustainable, low-emissions, intensification of maize production in sub Saharan Africa policy making - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The African Union Commission is using our research results on low-emissions intensification pathways for maize to prepare its Abuja 2 Summit on Fertilizers and Soil Health (2021). In our research we show that by sustainably increasing yields and nutrient use efficiency, >70 Mton CO2 equivalents could be saved by 2050 for maize production alone in 10 countries in SSA. The fertilizer industry is using these findings to drive market developments, suitable product formulations, and plant nutrition technologies and services.